2022
DOI: 10.1002/smll.202202242
|View full text |Cite
|
Sign up to set email alerts
|

Size Optimization of Organic Nanoparticles with Aggregation‐Induced Emission Characteristics for Improved ROS Generation and Photodynamic Cancer Cell Ablation

Abstract: Aggregation‐induced emission (AIE) fluorogens provide new opportunities to promote efficient reactive oxygen species (ROS) production in aggregates, which represent the promising candidates to construct theranostic nanoparticles for photodynamic therapy (PDT), but the size effect has been rarely explored. Herein, a universal method to fabricate organic nanoparticles with controllable sizes is reported and it demonstrates that ≈45 nm is the optimal size of AIE nanoparticles for PDT. Different from conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 53 publications
0
21
0
1
Order By: Relevance
“…TPE-BBT began to form large aggregates with a mean diameter ( d ) of 629 nm at f w = 20%, and the size of formed aggregates decreased when the f w increased to 50% ( d = 203 nm) or 90% ( d = 82 nm). The change of the aggregate size could be explained by the aggregation process, which typically includes initial nucleation, coalescence or agglomeration, and stabilization . The nucleation rate would be faster at a higher f w , resulting in smaller aggregates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TPE-BBT began to form large aggregates with a mean diameter ( d ) of 629 nm at f w = 20%, and the size of formed aggregates decreased when the f w increased to 50% ( d = 203 nm) or 90% ( d = 82 nm). The change of the aggregate size could be explained by the aggregation process, which typically includes initial nucleation, coalescence or agglomeration, and stabilization . The nucleation rate would be faster at a higher f w , resulting in smaller aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…The change of the aggregate size could be explained by the aggregation process, which typically includes initial nucleation, coalescence or agglomeration, and stabilization. 43 The nucleation rate would be faster at a higher f w , resulting in smaller aggregates. The absolute QYs of three aggregates in different f w were measured.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The results clearly demonstrated that the hydrophobic–hydrophilic balance and polymer structure within the amphiphilic polymeric assemblies greatly affects their ABDA interaction and degradation. Such a phenomenon was observed in a polymer photosensitizer with AIEgens as well. , In this work, b. G 100 B 2 T 5 shows good photophysical and chemical properties and better ABDA degradation and was selected for cellular experiments. In addition, G 100 and b. G 100 B 5 were used as controls.…”
Section: Resultsmentioning
confidence: 80%
“…Such a phenomenon was observed in a polymer photosensitizer with AIEgens as well. 34,35 In this work, b.G 100 B 2 T 5 shows good photophysical and chemical properties and better ABDA degradation and was selected for cellular experiments. In addition, G 100 and b.G 100 B 5 were used as controls.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…2001年,唐本忠院士首次发现并提出了聚集诱导发光(Aggregation-induced emission,AIE)现象 [9] , 作为AIE家族的"伯乐" ,他将AIE家族的人才介绍给世界各国认识,自此AIE家族美名远扬,逐步走 进了人们的视野之中。 这样一个名不见经传的家族一问世,便给了ACQ家族一记下马威,向它们展现了团结的力量。 六苯基噻咯(Hexaphenylsilole,HPS)作为AIE家族的长老,奉行"团结就是力量"的人生格言,它自 身呈现为独特的螺旋桨式构型,在稀溶液中单兵作战时发光微弱甚至观测不到,但团结起来便与 ACQ家族的各位截然不同,呈现出强而明亮的荧光(图2)。 图2 六苯基噻咯在不同比例的乙腈/水混合溶剂中的聚集诱导发光现象 [8] 因此,AIE家族最显著的优势便是团结--聚集态下的高效发光,恰好弥补了ACQ家族最大的缺 陷,这一特点也使得AIE家族逐渐成为人才市场上的潜力股。 AIE家族的问世为人们克服ACQ家族的痼疾开辟了一条新途径,也引发了众多学者的研究兴趣, 如致力于AIE家族在生物医学及能源中应用研究的刘斌教授 [10] 、 开发AIE家族新成员喹啉腈染料并用 于生物医学研究的朱为宏教授 [11] 、探索具有AIE特性聚合物的设计合成与应用的秦安军教授 [12] 、在 聚集体光电功能材料富有成就的李振教授 [13] 、 从事新型AIE材料的生物应用研究工作的王东教授 [14] 、 致力于开发疾病诊治新型AIE材料的丁丹教授 [15] 等杰出的科学家。 我国科学家为AIE家族的兴起付出了不懈的努力,不仅不断提出新型分子结构为AIE家族添砖加 瓦,还将AIE家族引入各大领域,带领AIE家族逐渐走向昌盛,经过二十多年的发展,AIE家族向ACQ 家族此前垄断的多个领域进军,如智能材料、液晶或偏振光材料、高效的OLED显示和照明材料、光 波导材料、生化传感材料、痕迹识别材料以及生物成像材料等,一跃成为了"新型人才培育之家" 。 2.2 AIE揭秘 AIE家族在这短短数十年间向各个领域输送了大批量的人才,家族的发展一片欣欣向荣,这也难 免引起了ACQ家族的不满,不惜向AIE家族发起挑战,质疑它们光学性质的可靠性。对此,AIE家族 特地举办了一场新闻发布会,深入地向人们阐述它们高效发光的秘密,来打消人们心中的疑虑。 主角正是AIE家族的明星"四苯乙烯(Tetraphenylethylene,TPE)" ,AIE家族介绍道: "TPE分子的 四个苯环(四个转子)连接到中心双键作为它的'四肢',当TPE均匀地分散在良溶剂中时, '四肢' 处于活跃的自由旋转状态,而且不断地与周围的溶剂相互作用,自身的能量主要以散热的形式耗散 (非辐射跃迁),从而导致发光微弱;在处于聚集态时,相邻的TPE分子彼此造成的约束会较大程度地 限制各个分子中'四肢'的运动,非辐射跃迁受到阻碍,自身的能量便主要以发光的形式耗散(辐射 跃迁),从而导致荧光增强,闪闪发光(图3)。"话音刚落台下掌声四起,新闻发布会顺利结束。 图3 四苯乙烯分子内运动受限发光机理 [8] 经过这场小风波,人们对AIE家族的好感不断增加,它们也不负众望,以更豪迈的姿态书写着家 族传奇。在AIE家族的不懈努力下,多个行业都能看见AIE族人的身影,它们的出现解决了ACQ家族 一直以来的难题,也使得它们在更多领域的应用及发展备受期待。…”
Section: Aie问世unclassified